Keragaman Karakteristik Morfologis Tanaman Kakao (Theobroma Cacao L.) Di Kecamatan Harau Kabupaten Lima Puluh Kota - Winesday Rindu; Gustian; Wulan Kumala Sari (Jurusan Budidaya Perkebunan, 2021)
Generally, the cacao farmers in Harau, Lima Puluh Kota District cultivating the cacao crops that unclear identity of its seed and there is also a high level of cacao diversity. Therefore the objectives of this study were to observe the morphological characters of cacao in Harau, Lima Puluh Kota District, and collecting data on the morphological characteristics of it as initial information on cacao germplasm development. This research was conducted by a survey, obtained information from the Agriculture Department, interviewed the cacao farmers, and collected data directly in the field. The method used in this research was a purposive sampling. The observed cacao crops as samples were taken from 3 Nagari in Harau, Lima Puluh Kota District, namely Nagari Taram with 4 cacao variants, Nagari Bukik Limbuku with 4 cacao variants, and Nagari Solok Bio-bio with 3 cacao variants. The obtained data were analyzed by NTSYS Program Ver. 02 which aims to know the diversities among them. The similarity of the phenotypes with a coefficient of 33-58 % and the variation is 42-67 %. Phenotypic variability of cacao crops on qualitative characters was a high value (41-85 %), and on quantitative characters was a moderate variability value ranges 3-50 %.